Analisis Efektivitas Teknik Lashing Container dalam Mengurangi Resiko Kerusakan Muatan pada Kapal MV. Tanto Bersinar - Nur Wahid Dino Setiawan; Arleiny Arleiny; Teguh Pribadi; Upik Widyaningsih (Pusat riset dan Inovasi Nasional, 2025)
This research aims to analyze the effectiveness of container lashing techniques in reducing the risk of cargo damage on MV. Tanto Bersinar. Lashing is a method of securing containers using equipment such as twist locks, lashing bars, and turnbuckle s to ensure cargo stability and safety during sea transport. The research employs a descriptive qualitative method with a case study approach through direct observation, interviews with crew members, and documentation. The findings indicate that the lashing technique on board has not been fully effective due to several factors, including insufficient quantity and poor condition of lashing equipment, limited crew understanding of proper procedures, and lack of regular training and supervision. The ineffectiveness of the lashing process leads to safety risks, operational delays, financial losses, and reputational damage to the company. This study recommends providing adequate and well-maintained lashing equipment, conducting routine crew training, ensuring compliance with standard operating procedures, and improving oversight to meet maritime safety standards. Proper implementation of lashing techniques is essential to minimize cargo damage and enhance the overall safety of maritime operations.